Expression of functionally different dectin-1 isoforms by murine macrophages. - Heinsbroek, SE; Taylor, P; Rosas, M; Willment, J; Williams, D; Gordon, S; Brown, G (2006)
Dectin-1 is a specific receptor for beta-glucans and a major receptor for fungal particles on macrophages (Mphi). It is a type II membrane receptor that has a C-terminal, NK-like, C-type lectin-like domain separated from the cell membrane by a short stalk region and a cytoplasmic immunoreceptor tyrosine-based activation-like motif. We observed functional differences in dectin-1-dependent recognition of fungal particles by Mphi from different mouse strains. RT-PCR analysis revealed that mice have at least two splice forms of dectin-1, generated by differential usage of exon 3, encoding the full-length dectin-1A and a stalkless Mphi dectin-1B. Mphi from BALB/c mice and genetically related mice expressed both isoforms in similar amounts, whereas Mphi from C57BL/6 and related mice mainly expressed the smaller isoform. NIH-3T3 fibroblast and RAW264.7 macrophage cell lines stably expressing either isoform were able to bind and phagocytose zymosan at 37 degrees C. However, binding by the smaller dectin-1B isoform was significantly affected at lower temperatures. These properties were shared by the equivalent human isoforms. The relative ability of each of the isoforms to induce TNF-alpha production in RAW264.7 Mphi was also found to be different. These results are the first evidence that dectin-1 isoforms are functionally distinct and indicate that differential isoform usage may represent a mechanism of regulating cellular responses to beta-glucans.